Processing and storage effects on anthocyanin composition and antioxidant activity of jams produced with Camarosa strawberry. (16th May 2013) - Amaro, Luís F.; Soares, M. Teresa; Pinho, Carina; Almeida, Isabel F.; Pinho, Olívia; Ferreira, Isabel M. P. L. V. O.
Summary Anthocyanin profiles and radical scavenging activity of Camarosa strawberry jams as affected by two processing methods (conventional/industrial) and storage conditions were evaluated. Industrial strawberry jam produced in a closed system with vacuum preserved the anthocyanin composition (the total content was 35.77 ± 2.56 mg per 100 g) when compared with conventional jam produced in an open system (3.35 ± 0.05 mg per 100 g). However, the radical scavenging activity of conventional jam was lower than that of industrial jam, as EC50 was 52.99 ± 0.94 and 44.33 ± 2.47 mg mL−1, respectively. Two‐way analysis of variance indicated a significant effect of processing method and storage time during 60 days and a significant interaction for all variables except for EC50. Long‐time storage of industrial jams at −8 °C leads to 80% reduction in anthocyanin content without loss of sensorial characteristics, whereas at room temperature the reduction was 98%, and the red colour was replaced by a brownish. Regardless of storage temperature, the radical scavenging activity of jams decreased 50–60% of its initial value.